AN ANALYTICAL STUDY OF THE STARTUP VILLAGE IN KALAMASSERY - Bindu P K and Devikrishna (Star Research Reach, 2016)
Global Entrepreneurship Monitor studies say that there is an impact of entrepreneurial activity on economic growth in various countries. Explaining about the entrepreneurship is not a simple task because no two entrepreneurs work activities are exactly alike. They search for change, respond to it, and exploit it. This paper discuss about the start-up village and the participants in the village. To make analyses about the entrepreneurial venture and to study their age, qualification level, funding, training etc. Entrepreneurs often have to make sacrifices to pursue their entrepreneurial dreams.